An Islamic Model for Taking Patients’ Spiritual History: Islamic Model of Taking Spiritual History - Memaryan, Nadereh; Rasouli , Maryam; Ghaempanah , Zeinab; Mehrabi , Maryam (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: In recent years, the spiritual dimension of human nature has received ever-increasing attention for better healthcare. One way of responding to this issue is taking the patients’ spiritual history in a healthcare setting. Spiritual history is a set of questions that can explore the spiritual experiences and beliefs of a patient with a simple interview. This study seeks to establish a new framework for obtaining spiritual history based on Islamic culture. The present study aimed to establish a new framework for obtaining the patients’ spiritual history by using a qualitative approach. Materials and Methods: For the qualitative study, first, the conceptual framework of spirituality was grounded by a team of experts. Then, a two-part questionnaire was developed based on the selected available tools and the Delphi method. Ethical Considerations: The principles of ethics and integrity in the research, citation, and literature analysis were taken into consideration. Findings: The 16 finalized questions were divided into two sections. In this regard, the first part was concerned about the beliefs, ethics, values, behaviors, and experiences related to spirituality, which can be used to derive the required spiritual information from all patients in any situation. The second part was developed based on the spiritual needs of the patients. Conclusion: As the findings indicated, taking spiritual history can facilitate the establishment of a more intimate relationship between the patient and therapist. It is hoped that the utilization of this Islamic model can improve the patients’ quality of life. *Corresponding Author: Zeinab Ghaempanah; Email: zeinab.ghaempana@gmail.com; ORCID: https://orcid.org/0000-0002-8291-0811 Please cite this article as: Memaryan N. Rasouli M. Ghaempanah Z. Mehrabi M. An Islamic Model for Taking Patients’ Spiritual History. Bioeth Health Law J. 2021; 1:1-8 (e23). http://doi.org/10.22037/bhl.v1i1.38185